Diastereoselective synthesis of 1,3-syn-oxazines via a tandem hemiaminalization and Tsuji-Trost reaction - Tang, Bin; Wang, Liang; Menche, Dirk (Synlett, 2013)
A novel domino sequence for the rapid assembly of 1,3-syn-substituted oxazines is reported. Mechanistically, the one-pot procedure is based on a three-step sequential process involving a hemiaminalization and Tsuji-Trost reaction. The process generates up to two new stereogenic centers in a concise and convergent fashion from simple and readily available starting materials.